Determination and analysis of time series of CFC-11 (CCl3F) from FTIR solar spectra, in situ observations, and model data in the past 20 years above Jungfraujoch (46°N), Lauder (45°S), and Cape Grim (40°S) stations. Issue 6 (10th October 2022) - Pardo Cantos, Irene; Mahieu, Emmanuel; Chipperfield, Martyn P.; Smale, Dan; Hannigan, James W.; Friedrich, Marina; Fraser, Paul; Krummel, Paul; Prignon, Maxime; Makkor, Jamal; Servais, Christian; Robinson, John
Abstract : Analysis of the last 20 years ground-based FTIR time series of CFC-11 from NDACC stations in the northern and southern hemispheres confirm the slowdown in the CFC-11 atmospheric concentration decay, related to emissions from non-reported production. Abstract : The atmospheric concentration of CFC-11 (CCl3 F) has declined in response to the phase-out of its production by the Montreal Protocol. Nevertheless, this atmospheric concentration decline suffered a slow-down around 2012 due to emissions from non-reported production. Since CFC-11 is one of the most important ozone-depleting chlorofluorocarbons (CFCs), its continuous monitoring is essential. We present the CFC-11 total column time series (2000–2020) retrieved in a consistent way from ground-based high-resolution solar absorption Fourier transform infrared (FTIR) spectra. These observations were recorded at two remote stations of the Network for the Detection of Atmospheric Composition Change (NDACC): the Jungfraujoch station (Northern Hemisphere) and the Lauder station (Southern Hemisphere). These time series are new. They were produced using improved line parameters and merged considering the instrument changes and setup modifications. Afterwards, they were compared with Cape Grim station in situ surface observations conducted within the Advanced Global Atmospheric Gases Experiment (AGAGE) network and with total column datasets calculated by the TOMCAT/SLIMCAT 3-D chemical transport model. Trend analyses were performed, using an advanced statistical tool, in order to identify the timing and magnitude of the trend change in both hemispheres. The observations are consistent with the model results and confirm the slowdown in the CFC-11 atmospheric concentration decay, since ≈2011 in the Northern Hemisphere, and since ≈2014 in the Southern Hemisphere.